Experimental investigation of the phases transitions on O-rich side of the Zr–O system. (December 2022) - Brunel, A.; Quaini, A.; Alpettaz, T.; Bonnet, C.; Guillou, R.; Cormier, L.
Abstract: In order to describe the complex reactions taking place during a severe accident in a PWR, the knowledge of the Zr–O system is critical. However, thermodynamic data are lacking concerning this system for oxygen rich compositions. The aim of this work is to obtain new experimental data on the liquidus/solidus transitions in the O-rich side of the Zr–O binary system. This work provides liquidus and eutectic transition temperatures for oxygen atomic fractions from x(O) = 0.28 to x(O) = 0.667. These data are used to validate the Zr–O thermodynamic model in the TAF-ID thermodynamic database. The current study confirms the eutectic transition temperatures (T = 2084 ± 51 °C) and its domain of existence. However, our measurements for x(O) > 0.6 suggest the existence of a congruent melting lying between x(O) = 0.65 and pure ZrO2, with an estimated value lower than the current calculation outcome from the TAF-ID. Highlights: New data on the high temperature liquidus/solidus transitions of the Zr–O binary system. The eutectic transition temperatures (T = 2084 ± 51 °C) and its domain of existence were confirmed by this study. The melting temperatures for ZrO2 and x(O) = 0.65 imply that a congruent melting may exist between these compositions.